A study on the influence of matrix distribution to the properties of polymer matrix composite (PMC) - Shahaneem, Sa'hari (2010)
This thesis deals with the composite materials, more focusing in Polymer Matrix Composite. Objective of this thesis is to investigate the influence of matrix distribution to the mechanical and physical properties of polymer matrix composite. Several testing is planned which are Tensile Test, Vickers Hardness Test and Density Test in order to study the behaviour of Polymer Matrix Composite (PMC) when their composition is varied. For this Project, fibreglass is use as the dry fiber and Epoxy resins as its matrix material. Hand layup process is use to fabricate the laminated composite. The specimens are divided into four major categories with different weight content percentage of fiber and matrix which are 30% matrix 70% fiber, 40% matrix 60% fiber, 50% matrix 50% fiber and lastly, 60% matrix 40% fiber. From the observation of matrix distribution, for category E1 (30% matrix 70% fiber), it can be seen that all fibers area were not fully distributed with matrix material due to less matrix content. For category E4 (60% matrix 40% fiber), it can be seen that the matrix content able to be distributed to the whole area of fibers but it need more time to cure. In addition, the result of Physical Testing shows that the density of laminated composite increased as the matrix amount increased. Moreover, from Mechanical Test it shows that tensile strength of laminated composite is increased as amount of matrix increased. As the result, the modulus of elasticity is increased too. From Stress-Strain Curve, it shows the brittle material behaviour of laminated composite. E4 have the highest tensile strength and modulus of elasticity while E1 have the lowest tensile strength and modulus of elasticity. Besides, E4 have the highest hardness number among the others. It can be conclude that, the properties of Polymer Matrix Composite is depends on the matrix distribution.